THE KUM PROGRAM (LITERACY ENTERPRISE) IN EMPOWERING THE COMMUNITY THROUGH TRAINING OF THE SALTED EGG MAKING COCONUT OIL (THE COLLABORATION OF LPPM OF DJUANSA UNIVERSITY WITH THE BOGOR DISTRICT OF GOVERNMENT EDUCATION AFFAIR) - Masithoh, Siti (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2015)
The literacy of independent business is upgrading literacy activities through learning business skills that can increase the productivity of individuals and groups independently for students who have attended the basic literacy competence training. The program provided is expected to be the provision of skills in raising the household economic level. The learners would have independence economic skill with the additional income. The implementation of KUM program was held in October-November 2014 which includes training salted egg and coconut oil making. It was conducted in village of Banjar Waru, Ciawi, Bogor. The participants had a good motivation during this program (evaluation of literacy and skills training). Learning by doing method considered as an essential task because people could practice the theory given directly. The result was useful enough, UNIDA through LPPM was booked and bought artificial and palm oil in order to enliven the result seminar of research and service in 2014. The obstacles encountered relatively be overcome, the time table should be adjusted based on the learning and lecturers schedule.